Legal Counseling on Child Abuse for Students in Singkawang City - Fadhil, Moh.; Lusiana, Vinna; Widiyawati, Ari; Ulya, Nanda Himmatul; Wibowo, Arif; Suhardiman, Suhardiman; Suryani, Tina Zulfa (DAS SEIN: Jurnal Pengabdian Hukum dan Humaniora (Journal of Legal Services and Humanities), 2025)
This study aims to provide understanding and legal counseling regarding child abuse in Singkawang City, West Kalimantan, with a focus on bullying, sexual violence, and child marriage. The counseling activity was carried out by the Faculty of Sharia at IAIN Pontianak at MAN Kota Singkawang and SMAN 2 Kota Singkawang in 2023. The implementation method consisted of three stages: preparation and administrative processes, field activities, and reporting the results. The delivery of the material was conducted through an interactive model and dialogue, interspersed with clips from the film A Silent Voice and reflections on the song Satu Satu. The results of the activity showed that participants gained an understanding of perpetrators, victims, and witnesses in cases of child abuse, as well as appropriate prevention and reporting mechanisms. Feedback from participants revealed that bullying and sexual violence are relevant issues in the school environment, with the main focus on prevention starting from oneself and the importance of building a healthy, equal, and inclusive friendship environment.